FIRST GENERATION AND FOURTH GENERATION CEPHALOSPORIN SUSCEPTIBILITY AGAINST CLINICAL ISOLATES - Adeel Arsalan; Syed Baquir Shayam; Rehan Pasha (Journal of University Medical & Dental College, 2016)
ABSTRACT: PURPOSE: Curing of infections is usually on the top priority of health associated-professionals. Resistance of microbes by antibiotics is worrying situation for medical professionals. Cephalosporins are one of the most commonly used β-lactam antibiotics. Cefepime and cephalexin are belonging to fourth and first generation cephalosporin respectively. The main aim of the present study is to evaluate the difference in resistance a pattern of pathogens between these two generations of anti-infective agents. METHOD: During the present study, in-vitro antibacterial activity of cefepime and cephalexin has been observed by Kirby-Bauer method (disk diffusion method). A sum of 91 clinical isolates of Staphylococcus aureus (43), Escherichia Coli (37), and Klebsiella pneumoniae (11) have been isolated from urine, stool, sputum and surgical, burn, and accidental wound pus from different hospitals at Karachi. RESULT: The present study has revealed that Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae has been shown 37.7%, 26.3%, and 34.8% resistance against cefepime, fourth generation cephalosporin respectively, while 77.4%, 91.7%, and 89.6% S. aureus, E. coli, and K. pneumoniae has been resistant against first generation cephalosporin, cephalexin. CONCLUSION: It has concluded from the present study, that cefepime 4th generation cephalosporin is far much better susceptibility as compared to cephalexin. The study has been strongly recommended the routine monitoring and observation of susceptibility of microbes against respective antibiotics before administration.